When I was solving some differential equations, I asked myself the following: Is there a function has the following: $$y'=y+1$$ $$y''=y+1$$ $$y'''=y+1$$ $$......$$ $$......$$

If the initial value is $$y(0)=1$$

  • 2
    $\begingroup$ What about $y=2e^x-1$? $\endgroup$
    – Galc127
    Dec 14, 2014 at 12:51
  • 1
    $\begingroup$ @Amzoti how does this only work for the first one? For any $k$, $y^{(k)} = 2e^x$ and $y(0) = 1$ so I think this one work. $\endgroup$
    – servabat
    Dec 14, 2014 at 13:01

3 Answers 3


Well you have that $$y'=y''=y^{(3)}\cdots$$ and the only function that is a derivative of itself is $ae^{x}$ for some $a$ so $y'=ae^x$ and $$y=y'-1=ae^x-1$$ Since $y(0)=1$ we have that $$y(0)=ae^0-1=a-1=1$$ so $a=2$ hence our function is $\boxed{y(x)=2e^x-1}$

  • 5
    $\begingroup$ +1, although the edge case mentioned doesn't need special consideration, since the function $y'=0$ is of the form $y'=ae^x$ with $a=0$. $\endgroup$ Dec 14, 2014 at 15:12
  • $\begingroup$ @PeterOlson Yes you're right,corrected,Thanks $\endgroup$
    – kingW3
    Dec 14, 2014 at 21:57

All your differential equations after the first one are implied by the first equation. If $y'=y+1$ then differentiation of it gives $y''=y'$ and further differentiation gives the successive equations. So it is really just about solving the first equation with the given initial value, and this you can do.


The solution to $$ y' = y + 1,\ y(0)=1$$ is $y = 2e^x -1$ which can be found from your method of choice for first-order non-homogeneous ODEs. Now let's see what the derivatives look like

$$y' = 2e^x$$

$$y'' = 2e^x$$

$$y''' = 2e^x$$

We can clearly see $y^{(k+1)} = y^{(k)}\ \forall k\in\mathbb{Z},k\geq1 $. Therefor all $n$th-derivatives of $y$ are equal by induction, and as $y'$ satisfies the conditions so do all $y^{(k)}$.


If you're interested, here's how you could solve this using annihilators, my method of choice for simple problems like this (I prefer Laplace for harder ones). First re-arrange the equation to say:


We find the general solution, $y_c$ by setting the RHS to $0$:

$$y_c'-y_c = 0$$

For which we assume $y_c = Ce^{mx} \Rightarrow mCe^{mx}-Ce^{mx} = 0 \Rightarrow m = 1$ so therefor $y_c = Ce^x$. We need to find $y_p$ now.

As $D$ annihilates $1$, assume $y_p = a$. Then $y' = 0$ and thus $0 - a = 1$ so $a=-1$. All together we have $y = Ce^x-1$. Further

$$y(0) = Ce^0 - 1 = 1 \Rightarrow C = 2 \therefore y= 2e^x -1$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.